METAPHORIC CONCEPTUALISATION OF PRIDE IN THE GEORGIAN LANGUAGE AND CULTURE - Rusieshvili-Cartledge, Manana; Dolidze, Rusudan; Keburia , Mariam; Totibadze, Sopio (Online Journal of Humanities ETAGTSU, 2023)
Metaphors express the cultural values of society and communicate their worldviews (Lakoff & Johnson, 2008). From this standpoint, the choice of metaphors to conceptualize emotions (for instance, PRIDE) is believed to be determined by universal and cultural-specific metaphoric models that arise from globally shared contexts on the one hand and cultural-specific contexts, practised locally and accepted by the speech-community, on the other (Kövecses, 2015). This paper explores the general models of metaphor and their specific manifestations employed while conceptualization the concept of PRIDE in the Georgian language and culture. The empirical data were collected from the Georgian National Corpus. The data were analysed employing the model of metaphor suggested by Rusieshvili (2005). Full Text (PDF)